Rail Corrugation Characteristics of Cologne Egg Fastener Section in Small Radius Curve - Zhiqiang Wang; Zhenyu Lei; Yang Zhao; Yao Xu (Shock and Vibration)
By analyzing the measured data of rail corrugation in a small radius curve track with Cologne fasteners, the typical passing frequencies of corrugation were obtained. Then, according to actual line conditions, the vehicle-track coupled model and rail material friction and wear model were established and simulated, and rail corrugation characteristics of the curved section were studied. The results show that the variation amplitude of creep force on the inside of a guiding wheelset is large, and it coincides with that of the saturated creep force partially and the coincident part appears periodically. The variation amplitude of creep force on the outside of the guiding wheelset is small, and it is approximately equal to that of the saturated creep force. In addition, the variation range of the wear depth curve on inner rail is mainly changing from 0 μm to 0.0014 μm, showing periodic wavy wear, and when the creep force is equal to the saturated creep force, the wear depth reaches the peak. The variation range of the wear depth curve on outer rail is mainly changing from 0.0005 μm to 0.0008 μm, showing uniform wear. Combined with the predicted profile of rail wear, it can be seen that the inner rail mainly suffers from corrugation on the top of rail and the outer rail mainly suffers from uniform wear on the side, which results in serious corrugation on inner rail and slight corrugation on outer rail. The frequency characteristics analysis of wear shows that the inner rail wear has characteristic frequencies similar to the passing frequencies. Modal analysis results show that the vibration of inner rail at the characteristic frequencies is greater than that of outer rail, which lead to the corrugation of the corresponding frequencies more easily. The wear growth rates at the characteristic frequencies are relatively large, which indicates that the wear at the corresponding frequencies will continue to develop and eventually form corrugation.